Toxic effects of 2, 3, 7, 8 tetrachlorodibenzo 1, 4 dioxin in laboratory workers. Issue 1 (February 1975) - Oliver, R M
Abstract : The toxic effects on three young scientists who had transient minimal exposure to 2, 3, 7, 8 tetrachlorodibenzo 1, 4 dioxin (dioxin) are described. Two of them suffered from typical chloracne. Delayed symptoms about two years after initial exposure occurred in two of the scientists. These symptoms included personality changes, other neurological disturbances, and hirsutism. All three scientists were found to have raised serum cholesterol but no other biochemical disturbances, and no porphyrinuria nor liver damage was demonstrated. The question whether the unusually delayed physiological effects were in fact due to the initial dioxin exposure is discussed. Although conclusive evidence is lacking, it seems likely that these delayed effects were in fact due to dioxin intoxication.